Extending Information Delivery Specifications for digital building permit requirements - Simon Fischer; Harald Urban; Christian Schranz; Patrick Loibl; Léon van Berlo (Developments in the Built Environment)
This paper examines the potential for extending the Information Delivery Specification (IDS) schema to facilitate its integration into the building permit process. IDS is an open specification for defining and verifying information requirements for digital building models. Building authorities have already begun utilising IDS to define information requirements for automated code compliance checks. However, this requires the filtering of elements beyond the current scope of IDS. Such filtering functionality also has the potential to facilitate simple code compliance checks. This paper presents concepts for extending IDS to define information requirements for escape route analysis and code compliance checks for Austrian fire resistance regulations. The main extension was the filtering of elements depending on characteristics of related elements. Nesting existing functionalities enabled the schema to remain simple. A prototype implementation demonstrated that minor extensions to the IDS schema can significantly enhance its functionality, paving the way for broader applications of IDS.